Եղիշե Չարենց – Նիկոլ Աղբալյան - Գասպարյան, Դավիթ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Նիկոլ Աղբալյանն առաջին իսկ գրական քայլերից նկատել էր բարձրացող հանճար Ե. Չարենցին և մտադիր էր նրան նվիրել հրապարակային դասախոսություն: Այդ հարցը քննարկել էր Հ. Թումանյանի հետ և ստացել նրա աջակցությունը: ՀՀ կառավարության մեջ Աղբալյանն ստանձնեց արվեստի և կրթության ոլորտը՝ ստեղծեց Հայ գրողների ընկերությունը, սատարեց «Պանդոկ» գրական խմբակի գործունեությանը: 1919 թ. հոկտեմբերի 16-ին Գրական ընկերությունը Պառլամետի դահլիճում հրավիրում է երեկոի: Ն. Աղ-բալյանը խոսել է մոտ մեկուկես ժամ և ըստ ամենայնի ներկայացրել և՛ թեմայով, և՛ պոետիկայով նոր բանաստեղծ Ե. Չարենցին: Ելույթ են ունեցել գրական տար-բեր հեղինակություններ: Չարենցը դարձել է որոնված անուն: Ինքը՝ Չարենցը, այդ երեկոյին ներկա չի եղել, քանի որ Կարսի մարզում զբաղված էր ուսուցչությամբ: Աղ-բալյանի զեկուցման մասին տեղեկանում է մամուլից և ավելի, քան երեք ամիս հետո ներկայանում նրան: Վերջինս նրան ջերմորեն է դիմավորում և նախարարությունում առաջարկում համեստ մի պաշտոն: Դժվար ժամանակներ էին. Աղբալյանը Չարենցին տալիս է ապրելու և ստեղծագործելու հնարավորություն: Այս երկու մեծությունների գրական առնչությունը հայ գրականության պատմության հիշարժան փաստ է։ 28 мая 1918 года была провозглашена Республика Армения. В новосозданном правительстве известный литературный критик Никол Агбалян курировал сферу искусства и образования. Им были созданы Литературное общество Армении и литературный клуб «Пандок». Н. Агбалян принимал активное участие в литературной жизни республики. 16 октября 1919 г. Литературное общество было приглашено в парламент. По данным периодики, в своем выступлении Агбалян представил Чаренца и его творчество. После этого вечера имя Чаренца стало востребованным. Сам Чаренц не присутствовал в зале, о выступлении Агбаляна он узнал из прессы, а спустя три месяца он приехал в Ереван и встретился с Агбаляном, предложившим ему скромную должность в министерстве. Это было сложное время. Н. Агбалян дал Чаренцу возможность жить и творить. За этот период Е. Чаренцем было создано много произведений, в частности, «Радиопоэма», изданная в 1920 г. при поддержке Н. Агбаляна. Чаренц проработал в министерстве до 1 июня 1920 года. Поэт при-соединился к коммунистическим силам, вместе с которыми приветствовал советизацию Армении и стал комиссаром искусств. Renowned Armenian literary critic Nikol Aghbalyan noticed the literary success of emerging genius Yeghishe Charents from the very beginning of his literary career and intended to dedicate a public lecture to him. He discussed this matter with Hovhannes Tumanyan as early as 1917 and received his support. On May 28, 1918, the Republic of Armenia was proclaimed, and Nikol Aghbalyan was one of its fighters. In the newly established government, he headed the sphere of arts and education and engaged in vigorous activities: he created the Society of Armenian Writers, founded the activities of the literary faction “Pandok”. In 1919, on October 16, the Literary Society was invited to an evening in the Parliament hall. According to the press, Aghbalyan spoke for about an hour and a half and, apparently, presented Charents, a new poet, from both thematic and poetic perspectives. The evening turned out to be very warm. Various literary authorities spoke at the event. After that evening, Charents’ name became in demand. Charents himself was not present that evening, as he was busy teaching in the village of Bashkyadiklar of Kars province. He learned about Aghbalyan’s speech from the press, and more than three months later, he came to Yerevan and introduced himself to Aghbalyan. Aghbalyan warmly welcomed him and offered him a modest position in the ministry. Those were difficult times. Aghbalyan gave Charents the op¬por¬tunity to live and create. During this time, Charents wrote many of his best works, among which “Radiopoem” was published as a separate book in 1920 with the support of Aghbalyan. Charents worked in the ministry until June 1, 1920. Before that, he joined the communist forces, welcomed the Sovietization of Armenia together with them, and became the commissar of arts. After the fall of the Republic of Armenia, Aghbalyan somehow left Armenia with other writers. After that, although Charents and Aghbalyan held different positions, they continued to collaborate. Charents sent him his new books, and Aghbalyan read and reviewed the demands of post-classical art. The literary connections of these great figures are a memorable fact in the history of Armenian literature.
Keywords: Philology